Новые виды клещей-фитосейид из Крыма (Parasitiformes, Phytoseiidae) - Колодочка, Л.А. (Вестник зоологии, 1979)
Two new species Kampimodromus kostini sp. n. and K. kuznetzovi sp. n. from the Crimea are described with illustrations, measurements and some ecological notes.